1996
DOI: 10.1046/j.1365-3024.1996.d01-104.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibabesial effect of the immunomodulator AS101 in mice: role of increased production of nitric oxide

Abstract: The immunomodulator AS101 has been shown to induce cell proliferation and to increase the secretion of a variety of cytokines. In the present study we evaluated the effect of AS101 on the pathogenicity of B. rodhaini infected mice. In order to clarify its mechanism of action we studied the ability of AS101 to activate neutrophils and macrophages, both of which inhibit parasite growth. More specifically, we studied the ability of AS101 to induce secretion of nitric oxide (NO). We found that AS101 protects mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Macrophage stimulation has been found to inhibit parasite growth in infected mice through the production of nitric oxide (185). Another macrophage soluble mediator, TNF-␣, has also been proposed to mediate parasite death in babesiosis (34).…”
Section: Host Immune Responsementioning
confidence: 99%
“…Macrophage stimulation has been found to inhibit parasite growth in infected mice through the production of nitric oxide (185). Another macrophage soluble mediator, TNF-␣, has also been proposed to mediate parasite death in babesiosis (34).…”
Section: Host Immune Responsementioning
confidence: 99%
“…The antimonial compounds, the first choice treatment to all forms of leishmaniasis has the disadvantage of both toxicity (pancreatitis, cardiotoxicity, hematological disorders, and skeletal muscle toxicity) and clinical resistance where they have been used for a long time [3,4]. Although a toxicity profiles of are not yet established, it can be expected that RT-01 may present similar non-or low toxicity as other organotellurane compounds due to lack of apparent toxicity of RT-01 in mice as reported in this study, excellent safety profile on clinical trials for cancer of other organotelluranes and the common tellurium-thiol chemistry of these compounds [8,13,14,21].…”
Section: Discussionmentioning
confidence: 64%
“…Organotellurane compounds present protease inhibition activity, which is specific for cysteine proteases, like papain and cathepsin B [7,8]. Various tellurane compounds have been described as presenting tumoricidal, antiviral, anti-protozoan parasite Babesia rodhaini activities, and immunomodulatory properties [7][8][9][10][11][12][13][14]21]. In addition to their effects, tellurium containing-compounds are characterized by low toxicity [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we examined the phagocytic activity of spleen mononuclear cells (MNC) and oxidative activity of spleen F4/80-positive macrophages (Mø) that might be involved in the therapeutic effect of CLM or diminazene diaceturate on Babesia rodhaini (B. rodhaini) infection in mice. Some workers have reported that the phagocytic and oxidative function of Mø might play an important role in the host protective mechanism in the murine model of babesiosis [4,7,9,11].…”
mentioning
confidence: 99%